1998
DOI: 10.1006/jeem.1998.1045
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Diminishing Marginal Existence Values

Abstract: This study addresses the debate over sensitivity of existence values as measured by contingent valuation to the scope of the good. We reconcile much of the debate within one theoretical model. If marginal WTP for existence goods is diminishing, then a given study that tested for sensitivity to scope over a range for which marginal WTP is high would be more likely to detect sensitivity to scope than another similar study that focused on a range for which marginal WTP is much lower. An empirical model is develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(64 citation statements)
references
References 18 publications
5
55
1
3
Order By: Relevance
“…That is, along the ESA improvement dimension, preferences appear to show scope insensitivity. This result was seen in 6 of the 9 cases where scope insensitivity could not be rejected and seems to be consistent with the diminishing marginal value argument discussed by Rollins and Lyke (1998). However, the argument for diminishing marginal utility does not fully explain the other three cases of scope insensitivity.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…That is, along the ESA improvement dimension, preferences appear to show scope insensitivity. This result was seen in 6 of the 9 cases where scope insensitivity could not be rejected and seems to be consistent with the diminishing marginal value argument discussed by Rollins and Lyke (1998). However, the argument for diminishing marginal utility does not fully explain the other three cases of scope insensitivity.…”
Section: Discussionsupporting
confidence: 67%
“…Rollins and Lyke (1998) showed that in the context of CV, scope tests may find scope insensitivity due to diminishing marginal utility. They argue that scope tests conducted over the upper range of a public good being valued may fail to identify scope effects because the comparisons are made over the range of the good where marginal utility approaches zero.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have demonstrated scope sensitivity (e.g., Carson and Mitchell, 1993;Smith and Osborne, 1996;Carson, 1997;Smith, Zhang and Palmquist, 1999), others have not (e.g., Diamond et al 1993;Boyle et al, 1994;Schkade and Payne, 1994;Beattie et al, 1998;Hammitt and Graham, 1999), while still others show that it is possible to observe scope sensitivity and scope insensitivity within the same study (Loomis, Lockwood and DeLacey, 1993;Rollins and Lyke, 1998;Schulze et al, 1998;Giraud, Loomis and Johnson, 1999;Bateman et al, 2004;Heberlein et al, 2005 3 ). This variety of findings has given ample support to both supporters and critics of CV.…”
Section: Consistency Versus Construction: the Scope Sensitivity Testmentioning
confidence: 99%
“…The test is failed in all of these studies except Nunes and Schokkaert, who pass their adding-up test when they use a factor analysis to account for warm glow, and not otherwise. Other studies have designs that support an adding-up test on non-incremental parts, but the authors do not report the results (Hoevengal, 1996;Loomis and Gonzalez-Caban, 1998;Riddel and Loomis, 1998;Rollins and Lyke, 1998;Streever et al, 1998).…”
Section: Introductionmentioning
confidence: 99%